Manning Roughness Coefficient Study on Bed Materials Non-Cohesive with Parameters Using Entropy to Open Channel Flow - Hari Wibowo (International Conference on Coastal and Delta Areas, 2015)
Application of entropy in open channel models presenting relevant aspects oftheoretical issues and practical useful for cross-sectional velocity distribution. The ratio between the average velocity and the maximum depends on the local morphology. Recent research has suggested formulation Manning roughness, n, based on the ratio and the ratio between the position where the velocity is zero and the maximum, y0/ymax, the flow depth of the flow regime. Based on the experience of stable flow, analysis entropy dependence on n parameters, and M for flow depth,proposes an equation y0/ymax to know the bed channel roughness coefficient. The results showed a good linear relationship between estimate n and n entropy calculation and n with the bedform. Obtained from linear regression analysis of the data relationships flume ncalculate= 0,5803netropi + 0,010 with good correlation (R2 = 0.864) using the entropy parameter ï†(M) = 0.8197, while for the data in a natural channel ncalculate = 0.754 netropy+ 0.006 with good correlation (R2 = 0.877) with ï†(M) = 0.914. It also has a fault tolerance (0.005 to 0.293)%, which is still below the tolerance.